Peculiarities of reaction of HIF-1α protein of the hippocampus neurons in rats with experimental diabetes mellitus in the dynamics of ischemic-reperfusion damage of the brain - Boychuk, T. M.; Nika, O. M.; Tkachuk, S. S. (Journal of Education, Health and Sport, 2016)
Boychuk Т. М., Nika О. М., Tkachuk S. S. Peculiarities of reaction of HIF-1α protein of the hippocampus neurons in rats with experimental diabetes mellitus in the dynamics of ischemic-reperfusion damage of the brain. Journal of Education, Health and Sport. 2016;6(12):906-915. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.260189 http://ojs.ukw.edu.pl/index.php/johs/article/view/4198 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016. PECULIARITIES OF REACTION OF HIF-1α PROTEIN OF THE HIPPOCAMPUS NEURONS IN RATS WITH EXPERIMENTAL DIABETES MELLITUS IN THE DYNAMICS OF ISCHEMIC-REPERFUSION DAMAGE OF THE BRAIN Т. М. Boychuk, О. М. Nika, S. S. Tkachuk Higher State Educational Establishment of Ukraine “Bukovinian State medical University”, Chernivtsi, Ukraine Abstract Introduction. The role of the transcriptional factor Hif-1α in pathogenesis of hypoxic damages and diabetes mellitus (DM) is proved, although molecular mechanisms underlying the basis of this factor dysfunction in association with DM with ischemic-reperfusion damage of the brain remain unknown. Objective. The objective of this investigation was to study the content of Hif-1α protein in the hippocampus neurons of rats with experimental DM in the dynamics of ischemic-reperfusion damage of the brain. Results. In rats without DM 20 minute ischemia with one hour reperfusion increases the content of Hif-1α protein in all the fields of the hippocampus. On the 12th day of ischemic-reperfusion period in the hippocampus CA2-CA4 fields the values of certain examined indices of the activity of Hif-1α transcriptional factor continue to increase, and in СА1field they normalize or approach to the values of animals in the control group. In rats with DM during early post-ischemic period there are no changes of Hif-1α protein content in CA1 field, in CA2 field there are signs of its reduced activity, in CA3 field they are limited by the reaction of one index, in CA4 field they are of a similar character with those of the control rats under experimental conditions. On the 12th day of ischemic-reperfusion period in CA1 field all the indices of activity of Hif-1α transcriptional factor increase exceeding corresponding indices by absolute values in animals of the control group under the same experimental conditions, in СА2 and СА3 fields changes of the examined parameters are limited as compared to the same ones in animals from the control group, in CA4 field values that were increased in the control group decrease. Conclusions. Diabetes mellitus restricts reaction of Hif-1α protein on ischemia-reperfusion inn the neurons of СА1-СА3 fields in early ischemic-reperfusion period and in the neurons of СА2-СА4 fields – on the 12th day of observation. Key words: hippocampus, diabetes mellitus, brain ischemia-reperfusion, Hif-1α protein.